Optic nerve head changes after short-term intraocular pressure elevation in acute primary angle-closure suspects - Jiang, Ran; Jonas, Jost B. (Ophthalmology, 2015)
To investigate changes in the optic nerve head morphology after acute intraocular pressure (IOP) elevation during a dark room prone provocative test (DRPPT). Prospective cohort study. Acute primary angle-closure (APAC) suspects underwent DRPPT. Study participants stayed in a dark room for 2 hours with the forehead placed on a desk. At baseline and within 5 minutes after DRPPT, tonometry and enhanced depth imaging by spectral-domain optical coherence tomography (SD OCT) were performed. Changes in 3-dimensional optic nerve head topography. The study included 114 eyes of 65 participants with a mean age of 58.3±8.7 years and a mean IOP elevation of 10.1±10.9 mmHg during DRPPT. When all eyes were included, the mean value of most optic disc parameters did not change significantly, except for a decrease in the temporal minimal rim width (P = 0.005). By including only eyes with an IOP increase greater than 15 mmHg, the mean value of cup width (P = 0.001) and cup depth (P = 0.002) increased, whereas the lamina cribrosa (LC) thickness (P = 0.035), temporal minimal rim width (P = 0.001), and nasal minimal rim width (P < 0.001) decreased. The LC depth and Bruch's membrane opening (BMO) did not differ between the baseline and the end of DRPPT. An IOP increase was significantly associated with widening (P < 0.001; r = 0.46) and deepening (P < 0.001; r = 0.52) of the optic cup, thinning of the LC (P = 0.003; r = −0.35), temporal minimal rim width (P < 0.001; r = −0.34), and nasal minimal rim width (P < 0.001; r = −0.35). Angle-closure suspect eyes showed a widening and deepening of the optic cup, decrease in neuroretinal rim width, and thinning of the LC after a darkness-induced IOP increase of >15 mmHg. The diameter of the BMO and position of the anterior LC surface remained unchanged. This suggests that a short-term IOP increase leads to a condensation of neuroretinal rim, prelaminar tissue, and LC, without major changes in the optic disc size and position of the anterior LC surface.